Fuel Injection in Automotive Engineering - Lejda, Kazimierz; Wos, Pawel (IntechOpen, 2012)
The main topic of "Fuel injection in automotive engineering" book is fundamental process that determines the development of internal combustion engines and performances of automotive vehicles. The book collects original works focused on up-to-date issues relevant to improving injection phenomena per se and injection systems as the engine key components.